Patient perceptions of success in obesity treatment: An IMI2 SOPHIA study - E. Farrell; J. Nadglowski; E. Hollmann; C. W. le Roux; D. McGillicuddy (Wiley, 2024)
Abstract Background It is anticipated that by 2030, 20% of the world's population will live with obesity. Success in the management of obesity is predominately determined in terms of BMI or percentage weight loss, yet the limitations of these have been widely recognized. This study aimed to understand patient definitions of success in obesity treatment. Methods A series of in‐depth focus groups, carried out with n = 30 adults living with obesity, offered a qualitative insight into patient definitions of success. Results A thematic analysis of data yielded four thematic findings: Success as freedom from stigma, bias and the mental burden of obesity; success as being able to participate fully in the world; success as measured by NSVs [non‐scale victories]; and success is not a number on a scale. Conclusions What this study highlights is (1) how current measures of success do not accurately encompass the priorities of people living with obesity, (2) the importance of addressing the psychological and emotional aspects of living with obesity in any definition of success , and (3) the importance of meaningful co‐creation of goals and indicators of success between clinician and patient for the effective management of the disease of obesity.